2019
DOI: 10.1038/s41584-019-0219-5
|View full text |Cite
|
Sign up to set email alerts
|

HLA associations in inflammatory arthritis: emerging mechanisms and clinical implications

Abstract: Our understanding of the mechanisms underlying HLA associations with inflammatory arthritis continues to evolve. Disease associations have been refined, and interactions of HLA genotype with other genes and environmental risk factors in determining disease risk have been identified. This Review provides basic information on the genetics and molecular function of HLA molecules, as well as general features of HLA associations with disease. We summarise evidence for various peptidedependent and peptide-independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 240 publications
1
53
0
2
Order By: Relevance
“…A possible precedent for the latter mechanism has been found, albeit in the opposite direction: CatD levels were shown to be elevated in the skin of CatL-deficient mice (80). Adaptation to a chronic lack of active CatD might help to explain why previous studies in CatD knockout mice (40) MHCII allelic variation is a major determinant of autoimmune disease risk (22,(81)(82)(83).…”
Section: Discussionmentioning
confidence: 99%
“…A possible precedent for the latter mechanism has been found, albeit in the opposite direction: CatD levels were shown to be elevated in the skin of CatL-deficient mice (80). Adaptation to a chronic lack of active CatD might help to explain why previous studies in CatD knockout mice (40) MHCII allelic variation is a major determinant of autoimmune disease risk (22,(81)(82)(83).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have since shown that, together, SE alleles are associated with more severe RA as well as developing ACPAs . On the other hand, HLA‐DRB1*03, *08 , and other alleles encoding for a DERAA motif in this same position on the HLA‐DRβ chain tend to be associated with seronegative RA . In addition to the MHC locus, SNPs in other genes have also been linked to an increased risk for developing RA in certain ethnic populations.…”
Section: Geneticsmentioning
confidence: 99%
“…The majority of the genetic susceptibility to SpA is attributed to the HLA class I family of HLA‐B27 alleles, especially the HLA‐B*27:02, *27:04, and *27:05 variants . Studies have also found associations with other HLA‐B alleles such as HLA‐B*40:01 and HLA‐B*47:01 , and with the HLA‐A , HLA‐DPB1 , and HLA‐DRB1 loci (reviewed elsewhere ref.…”
Section: Geneticsmentioning
confidence: 99%
See 2 more Smart Citations